Technical Evaluation and Improvement Strategies for Banjardowo Leachate Treatment Plant, Jombang District - Masteryna Maghfirahdina; IDAA Warmadewanthi (Dampak, 2026)
Banjardowo Landfill in Jombang Regency is equipped with a Leachate Treatment Plant (LTP) with a treatment capacity of 300 m³/day to prevent environmental pollution from landfill leachate. However, fluctuations in leachate characteristics and operational conditions may affect treatment performance over time. Monitoring results in 2025 indicated that Total Nitrogen concentrations in the treated effluent still exceeded the applicable discharge standard, suggesting that the treatment process had not yet achieved optimal performance. Therefore, this study aimed to evaluate the technical performance of the Leachate Treatment Plant at Banjardowo Landfill and formulate improvement strategies to support sustainable and effective leachate management. This study employed a descriptive quantitative approach through field observations, measurements of treatment units, reviews of technical and operational documents, stakeholder questionnaires, and leachate quality analyses conducted during the dry and rainy seasons. The technical performance evaluation was carried out by comparing the existing conditions of treatment units with established design criteria and assessing pollutant removal efficiencies. Furthermore, SWOT analysis was subsequently used to identify internal and external factors affecting plant performance and to formulate appropriate improvement strategies. The technical evaluation revealed that the LTP performance was not fully optimal due to excessive HRT in the Leachate Storage Pond, insufficient biofilter media volume, suboptimal DO and MLSS concentrations in biological treatment units, and operational instability in nitrogen removal processes. The UF unit effectively removed TSS and cadmium, while the constructed wetland served as a polishing unit. During the dry season, the removal efficiencies of BOD, COD, TSS, Total Nitrogen, Cd, and Hg were 59.2%, 58.4%, 98.2%, 17.2%, 89.7%, and 95.5%, respectively. During the rainy season, the removal efficiencies were 71.0%, 86.1%, 98.7%, and 99.6%, while no removal was reported for Cd and Hg, thus ensuring compliance with wastewater standards. The SWOT analysis places LTP in Quadrant III (recovery strategy) with coordinates (-0.22; 0.30), so the strategies that need to be implemented are (1) improving the aeration system and optimizing the nitrification-denitrification process and (2) rehabilitating artificial wetlands and strengthening the monitoring system.